What women want. Gender-based norms and cognition in STEM occupational choices - Matija Kovacic; Cristina Elisa Orso (Global Labor Organization (GLO), 2024)
This research investigates why some women like STEM occupations more than others. We show that this phenomenon is rooted in historical kin-based norms and specific aspects of cognition, perceptions, and aspirations enforced by the normative demands of ancestral societies. Using a sub-population of second-generation immigrants from the European Social Survey (ESS), we find that intensive kinship ties, supported by strong cousin-marriage preferences, co-residence of extended families, and community endogamy, which resulted in the enforcement of stricter social norms and greater conformity while discouraging individualism, independence, and analytical thinking, had a persistent negative impact on women's current STEM occupation choices. In addition to the individual-level analysis, we also document that kinship intensity reduces the proportion of women in STEM across countries, thereby widening the documented gender gaps. Furthermore, we show that the causal link between norms, cognition, and occupation is both direct and indirect, passing through contemporary cultural traits. At the same time, ancestral kin does not significantly affect men's occupational choices, while it increases the likelihood of having a gender-biased opinion about the role of women in the labour market. The results are robust to a rich set of potential confounding factors at the country of origin level and a battery of sensitivity checks.
Keywords: D03; J16; N30; 330; Kin-based institutions; gender-based norms; analytic cognition; STEM